SEJARAH PERKEMBANGAN PARIWISATA GEOSITE SIPINCUR SEBAGAI DESTINASI SUPER PRIORITAS WISATA DI HUMBANG HASUNDUTAN - Arfan Diansyah; Rapmaita Lamaida Simamora; Juliyanti Pakpahan; Ika Sinurat; Dwirja Aditya Daulay; Beatrix Sidabutar (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
The Sipincur Geosite is one of the Toba calderas in Humbang Hasundutan, precisely in Pearung Village, Paranginan District. Sipincur Geosite is a natural tourist destination filled with Tusam (pine) plants. A tourist destination that offers beautiful natural views, plants and Lake Toba, makes the Sipincur Geosite visited by many tourists. The opening of the Sipincur Geosite started at the same time as Humbang Hasundutan from North Tapanuli bloomed in 2003. The Sipincur Geosite, which is taken from the word